2012
DOI: 10.1002/app.36458
|View full text |Cite
|
Sign up to set email alerts
|

Arabinose content of arabinoxylans contributes to flexibility of acetylated arabinoxylan films

Abstract: Arabinoxylans (AX) from rye were partly debranched by chemical hydrolysis methods, and AXs differing in arabinosyl substitution were acetylated using chemical methods. The resulting materials are film forming, and these films underwent molecular structural analysis and were tested for their material properties. The composition and structure of the modified polymers were determined using high performance anion exchange chromatography and two dimensional nuclear magnetic resonance; it was shown that all free hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 30 publications
1
42
0
Order By: Relevance
“…Based on swelling measurements, previous studies reported the pore size of AX gels in the range 48–221 nm . In the present study, the width of AX strands forming the sponge‐like structure ranged from 30 to 60 nm, which is similar to that reported in hemicelluloses from bamboo . Figure presents the AFM image of non‐cross‐linked AX, which exhibits a height of 1.8 nm, suggesting the involvement of 1 or 5 AX chains.…”
Section: Resultssupporting
confidence: 86%
“…Based on swelling measurements, previous studies reported the pore size of AX gels in the range 48–221 nm . In the present study, the width of AX strands forming the sponge‐like structure ranged from 30 to 60 nm, which is similar to that reported in hemicelluloses from bamboo . Figure presents the AFM image of non‐cross‐linked AX, which exhibits a height of 1.8 nm, suggesting the involvement of 1 or 5 AX chains.…”
Section: Resultssupporting
confidence: 86%
“…Tensile tests showed that the strain at break, which reflects the flexibility of the films, was significantly higher at higher arabinosyl substitution levels. The elastic Young's modulus was not significantly affected, although a tendency was seen toward a less stiff material at higher arabinosyl substitution [197].…”
Section: Packaging Filmsmentioning
confidence: 79%
“…Purified hemicelluloses have fewer commercial applications than cellulose and lignin, but in recent years, interest in production of value-added products, such as xylitol [192][193][194][195][196], packaging films [197][198][199] and hydrogels [200][201][202][203][204][205][206][207][208][209] based on hemicelluloses has increased. Xylitol is used for sweetening owing to its dietetic and anticariogenic properties.…”
Section: Hemicellulosic Polysaccharidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Acetylated hemicellulose films have been used for food packaging . Apart from opening up opportunities for marketing renewable and biodegradable materials, chemical and physical protection of food can be achieved through food packaging with hemicellulose‐based materials.…”
Section: Hemicellulose Hydrophobizationmentioning
confidence: 82%